Issues in shipping's future: Need for, and prospects of, liner conferences - Paul Burke (Intereconomics, 1976)
This paper examines the need for liner conferences, or cartels, in international shipping, and compares investment in shipping to investment in housing, an industry which is not usually organized into private cartels. Then the paper discusses how the quantity of goods being shipped is likely to grow in the future, and how that growth can be expected to affect shipping conferences.
Keywords: 330; Shipping